Face Recognition Using Machine Learning Algorithm Based on Raspberry Pi 4b - Sunardi, Sunardi; Fadlil, Abdul; Prayogi, Denis (International Journal of Artificial Intelligence Research, 2022)
Machine learning is one of artificial intelligence that is used to solve various problems, one of which is classification. Classification can separate a set of objects based on certain characteristics. This study discusses the classification of objects in the form of facial images with the aim of the system being able to recognize a person's face to access a room for security reasons. The application of machine learning using the support vector machine algorithm with the support vector classifier technique is implemented on a raspberry pi-based security device. Â The results of training using this algorithm produce a model with 99% accuracy in 0.10 seconds based on testing data of 525 face images. The model evaluation got 99% precision, 99% recall, and 99% f1-score. Testing the model made from the training process using the raspberry pi model 4b is can recognize facial images in real-time. Â If the security device detects someone at the door and then recognizes the face image then room access will be granted and an alarm is activated indicating the door is open.